2016
DOI: 10.1038/srep22655
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic secondary degeneration in the spinal cord and ventral root after a focal cerebral infarction among hypertensive rats

Abstract: Cerebral infarction can cause secondary damage to nonischemic brain regions. However, whether this phenomenon will appear in central nervous system regions outside the brain remains unclear. Here we investigated pathological changes in the spinal cord and ventral root after ischemic stroke. All rats exhibited apparent neurological deficits post-MCAO, which improved gradually but could still be detected 12-weeks. Neuronal filaments in the corticospinal tract (CST) and neurons in the ventral horn were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…24) Our previous study showed that activated spinal microglia is observed in BCAO model mice. 9) In general, activated microglia releasing inflammatory cytokines is considered to be involved in the exacerbation of functional recovery after stroke and in the development of chronic pain. 10,25,26) Therefore, it was possible that the upregulation of spinal DDAH1 may be induced by microglial activation, which was observed in BCAO model mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24) Our previous study showed that activated spinal microglia is observed in BCAO model mice. 9) In general, activated microglia releasing inflammatory cytokines is considered to be involved in the exacerbation of functional recovery after stroke and in the development of chronic pain. 10,25,26) Therefore, it was possible that the upregulation of spinal DDAH1 may be induced by microglial activation, which was observed in BCAO model mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because, our previous study have shown that increment of spinal HMGB1 signaling induced upregulation of NOS activity on day 3 after BCAO. 9) It has been previously reported that the i.t. administration of L-NAME completely reversed the reduction of paw withdrawal threshold induced by intraperitoneal administration of oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SND involves the progressive death of neurons that were connected to the site of infarction but not initially damaged by the stroke. SND unfolds over a longer time scale than the infarction process and has recently been implicated as a potential modulator to a number of late phase functional recovery disturbances (Chen, Garcia, Huang, & Constantini, ; Dang et al, ; Fernandez‐Andujar et al, ).…”
Section: Introductionmentioning
confidence: 99%